2016
DOI: 10.1016/j.cbpc.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Is altered behavior linked to cellular energy regulation in a freshwater mussel (Elliptio complanata) exposed to triclosan?

Abstract: Environmental stress may alter the bioenergetic balance of organisms by resulting in greater energy investment into detoxification processes, which diverts energy from other biological functions. Here, we examine responses to triclosan (TCS) exposure in a freshwater mussel across multiple biological levels: behavioral (e.g., burrowing and movement activity), organismal (e.g., metabolic rate and heart rate), and subcellular (e.g., gene expression and protein abundance/activity). At the subcellular level, we emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…exposed to DIC (Schmidt et al, 2011); and Dreissena polymorpha exposed to DIC (Quinn et al, 2011). Similar results were also observed for the species mussels Elliptio complanata exposed to TCS (Goodchild et al, 2016) and Unio tumidus exposed to TCS (Falfushinskaya et al, 2015), indicating that the effects of both PPCPs were also observed at freshwater conditions.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
See 1 more Smart Citation
“…exposed to DIC (Schmidt et al, 2011); and Dreissena polymorpha exposed to DIC (Quinn et al, 2011). Similar results were also observed for the species mussels Elliptio complanata exposed to TCS (Goodchild et al, 2016) and Unio tumidus exposed to TCS (Falfushinskaya et al, 2015), indicating that the effects of both PPCPs were also observed at freshwater conditions.…”
Section: Accepted Manuscriptsupporting
confidence: 81%
“…The occurrence in the environment has been addressed (Bonnefille et al, 2018;Dann and Hontela, 2011;Fabbri and Franzellitti, 2016), revealing removal rates in waste water treatment plants (WWTPs) up to 99 % for Triclosan and 80% for Diclofenac (Wang et al, 2018;Zhang et al, 2008) and concentrations ranging from ng/L to µg/L in sewage treatment plants influents and effluents, rivers, groundwater, and coastal areas (Al Aukidy et al, 2012;Gaw et al, 2014;Lolic et al, 2015;Mezzelani et al, 2016;Olaniyan et al, 2016;Pal et al, 2010). In what regards to the effects of PPCPs in aquatic organisms a limited number of studies have evaluated water exposures at realistic concentrations of TCS (Gatidou et al, 2010;Matozzo et al, 2012) and DIC (Fontes et al, 2018;Gonzalez-Rey and Bebianno, 2014;Goodchild et al, 2016;Mezzelani et al, 2016;Mezzelani et al, 2018;Munari et al, 2018;Schmidt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…TCS induced immunosuppression in clams at low nanomolar concentrations via disruption of hemocytes and induction of DNA fragmentation (Matozzo et al 2012). TCS also produced a change in bioenergetic state in mussels exhibited as a decrease in animal activity via movement but an elevation in protein level detoxification markers (Goodchild et al 2016). At concentrations between 0.2 and 0.5 μM antimicrobial, histological alterations in liver and genes involved in lipid metabolism and detoxification were noted in toad tadpoles (Chai et al 2017).…”
Section: Triclosan Exposure Levels In Animalsmentioning
confidence: 99%
“…The respective primers used are listed in Table 1. We used Alien QRT-PCR Inhibitor Alert (Agilent Technologies, La Jolla, California, USA) as a non-endogenous RNA sample in place of a housekeeping gene for transcript normalization as described by Goodchild et al (2016). Gene expression results were normalized to these internal alien RNA levels for each sample, and all data were then normalized to the red control group.…”
Section: Quantitative Real-time Pcrmentioning
confidence: 99%